Arranjos institucionais e desenvolvimento: O papel da coordenaç\~ao em estruturas híbridas - Ronaldo Fiani (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The purpose of this paper is to examine the significance of institutional arrangements to development policies. Unfortunately, modern institutionalism has concentrated on the consequences of political and economic liberties (determined by the institutional environment) to development, with inconclusive results. It will be argued that institutional arrangements offer a much more promising and interesting possibility, providing useful analytical instruments for public policies when there is the need of cooperation from private agents, specially the concept of hybrid arrangements first elaborated by Oliver Williamson and then refined by Claude Ménard. The analysis proceeds first by discussing the difficulties faced by the theories that assert a clear-cut relation between institutional environment and development. Then the analysis then considers the conceptual difference between institutions and policies. It is then discussed the relevance of institutional arrangements to development policies involving private agents. Finally, selected evidence is presented in support of the argument of the relevance of institutional arrangements.
Keywords: B52; D23; O17; O25; 330; institutions; institutional arrangements; governance structures; development; public policy